2013
DOI: 10.1016/j.jacc.2013.02.071
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiopoietic Stem Cell Therapy in Heart Failure

Abstract: The C-CURE trial implements the paradigm of lineage guidance in cell therapy. Cardiopoietic stem cell therapy was found feasible and safe with signs of benefit in chronic heart failure, meriting definitive clinical evaluation. (C-Cure Clinical Trial; NCT00810238).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
170
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(176 citation statements)
references
References 58 publications
5
170
0
1
Order By: Relevance
“…Regenerative medicine has been developed in recent years, such as mesenchymal stem cell (MSC) transplantation to repair myocardial infarction (MI) and restore heart function in both animal experiments1, 2, 3, 4 and patients 5, 6, 7, 8, 9, 10. There is mounting evidence that MSCs help repair or regenerate damaged tissues, primarily by means of secreting paracrine factors,11 including antiapoptotic factors,12 proangiogenic factors,13 and exosomes,14 rather than via the differentiation into cardiomyocytes 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…Regenerative medicine has been developed in recent years, such as mesenchymal stem cell (MSC) transplantation to repair myocardial infarction (MI) and restore heart function in both animal experiments1, 2, 3, 4 and patients 5, 6, 7, 8, 9, 10. There is mounting evidence that MSCs help repair or regenerate damaged tissues, primarily by means of secreting paracrine factors,11 including antiapoptotic factors,12 proangiogenic factors,13 and exosomes,14 rather than via the differentiation into cardiomyocytes 15, 16, 17…”
Section: Introductionmentioning
confidence: 99%
“…While the safety of both autologous and allogeneic MSCs is reasonably well established, studies have demonstrated that allogeneic MSCs derived from young, healthy donors are more efficacious 1, 5, 6. Notably, these cells are shown to be a safe method to improve cardiac structure and function in preclinical and clinical trials 1, 2, 7, 8, 9, 10, 11, 12. The question remains: In which pathologic setting are MSCs most effective?…”
Section: Introductionmentioning
confidence: 99%
“…61 In a different approach, Terzic and colleagues exposed autologous MSCs to a cocktail consisting of TGF-β, FGF2, and other cardiopoietic factors prior to transplanting them in patients with heart failure through endomyocardial injections. [62][63][64] At six months, LVEF was improved and LVESV was decreased in the group that underwent cell transplantation, compared to the control group. Moreover, the group that received cell therapy showed improvements in a 6-min walk test, quality of life, and physical performance compared to other groups.…”
Section: -55mentioning
confidence: 94%